2014
DOI: 10.4025/actascibiolsci.v36i4.22852
|View full text |Cite
|
Sign up to set email alerts
|

<b>Experimental study on the efficiency of different types of traps and baits for harvesting <i>Macrobrachium amazonicum</i> (Heller, 1862)

Abstract: Macrobrachium amazonicum is a freshwater prawn endemic to South America with wide distribution in Brazilian Amazon rivers. In estuary and freshwater streams of the Pará State, they are captured with different types of traps locally know matapi. This study evaluated the efficiency of traps of different sizes (large, medium and small) and baits (babassu coconut and fish) for sampling this shrimp. Samplings were conducted with 24 traps with different treatments (trap size and bait). We captured 909 specimens. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Due to the existence of morphotypes, M. amazonicum populations generally have larger males than females (Silva et al, 2005;Flexa et al, 2005;Bentes et al, 2011). This occurs mainly in populations with marked intraspecific competition, where the sex ratio approaches 1:1 (Bentes et al, 2014). Although in these populations with morphotypes the maximum size occurs in males, the mean size of females is usually larger (Freire et al, 2012;Bentes et al, 2014).…”
Section: Population Structure and Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the existence of morphotypes, M. amazonicum populations generally have larger males than females (Silva et al, 2005;Flexa et al, 2005;Bentes et al, 2011). This occurs mainly in populations with marked intraspecific competition, where the sex ratio approaches 1:1 (Bentes et al, 2014). Although in these populations with morphotypes the maximum size occurs in males, the mean size of females is usually larger (Freire et al, 2012;Bentes et al, 2014).…”
Section: Population Structure and Mortalitymentioning
confidence: 99%
“…This occurs mainly in populations with marked intraspecific competition, where the sex ratio approaches 1:1 (Bentes et al, 2014). Although in these populations with morphotypes the maximum size occurs in males, the mean size of females is usually larger (Freire et al, 2012;Bentes et al, 2014). Larger males are uncommon among other palaemonids that do not have Downloaded from https://academic.oup.com/jcb/article-abstract/37/2/131/3089767 by Universidade Estadual Paulista J�lio de Mesquita Filho user on 24 June 2019 morphotypes (Bentes et al, 2011), and the absence of these in M. amazonicum populations is related to the aggregate distribution of the species in marshland environments (Pantaleão et al, 2012), such as those observed at the collection site.…”
Section: Population Structure and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Maciel and Valenti (2009), the occurrence of such morphotypes is related to the local population traits. The morphotypes may mostly occur in populations with intense intraspecific competition and sex ratio close to 1:1 (Bentes et al 2014). The absence of such morphotypes is more common in populations in which individuals show an aggregate distribution, as it occurs in muddy environments (Pantaleão et al 2012), with a great abundance of food and females.…”
Section: Discussionmentioning
confidence: 99%
“…There are around 20 species registered in Brazil (Mantelatto et al 2016), from which several are among the most economically important ones, such as Macrobrachium carcinus (Linnaeus 1758), Macrobrachium acanthurus (Wiegmann 1836) and Macrobrachium amazonicum (Heller 1862), (Valenti 1985), and the exotic invasive species Macrobrachium rosenbergii (De Man 1879), which was accidentally introduced as a consequence of their cultivation (Iketani et al 2016). Macrobrachium specimens are used as a protein resource by human obtained in nature-fishing activities or shrimp farming (Maciel and Valenti 2009;Bentes et al 2014;Costa et al 2016;Taddei et al 2017a).…”
Section: Introductionmentioning
confidence: 99%